Rgensi Meratifikasi Framework Convention On Tobacco Control (FCTC) Dalam Upaya Pengendalian Konsumsi Tembakau Di Indonesia - Kurniawan, Fajar (Jurnal Hukum & Pembangunan, 2023)
The current problem of tobacco consumption has become a global issue that covers almost all aspect of life, both economic, social and community welfare aspects, especially for the health aspects because of the impact of the healt losses they cause. Cigarette consumption in Indonesia continues to experience a significant increase. Indonesia is the thrid country with the highest number of smokers in the world. Global tobacco consumption control has been stated in Framework Convention on Tobacco Control (FCTC) since 2003, but until now Indonesia has not ratified that FCTC. As part of the civilization of the international community, it is proper for Indonesia to support effort to protect the public from dangers of tobacco consumption by immediately ratify FCTC into law. This is very important considering that public health protection efforts are part of the enforcement of human rights in health sector.